2015
DOI: 10.1074/jbc.m115.665489
|View full text |Cite
|
Sign up to set email alerts
|

ATDC (Ataxia Telangiectasia Group D Complementing) Promotes Radioresistance through an Interaction with the RNF8 Ubiquitin Ligase

Abstract: Background: ATDC/TRIM29 promotes resistance to ionizing radiation, but the factor(s) that mediate this effect are incompletely understood. Results: ATDC/TRIM29 binds to RNF8, promoting DNA repair and resistance to IR. Conclusion: Following DNA damage, ATDC/TRIM29 is phosphorylated and interacts with RNF8, promoting DNA repair and cell survival. Significance: The interaction between ATDC/TRIM29 and RNF8 is novel and is important for the DNA damage response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…A recent study reports that ATDC is essential for TP63‐regulated basal cancer invasive program . Moreover, ATDC exerts its oncogenic effect by promoting the radio‐resistance and chemo‐resistance of tumour cells . Consistent with these findings, our study demonstrated that ATDC was highly expressed in HCC cell, suggesting a potential oncogenic function of ATDC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent study reports that ATDC is essential for TP63‐regulated basal cancer invasive program . Moreover, ATDC exerts its oncogenic effect by promoting the radio‐resistance and chemo‐resistance of tumour cells . Consistent with these findings, our study demonstrated that ATDC was highly expressed in HCC cell, suggesting a potential oncogenic function of ATDC.…”
Section: Discussionsupporting
confidence: 90%
“…34 Moreover, ATDC exerts its oncogenic effect by promoting the radioresistance and chemo-resistance of tumour cells. [35][36][37] Consistent with these findings, our study demonstrated that ATDC was highly expressed in HCC cell, suggesting a potential oncogenic function of ATDC. Functional experiments showed that the knockdown of ATDC impeded the growth and invasion of HCC cells, while the overexpression of ATDC promoted HCC cell growth and invasion.…”
Section: Discussionsupporting
confidence: 88%
“…A recent report showed that the interaction of TRIM29 phosphorylated at Ser550 with RNF8 upregulates DNA damage responses (DDR), including H2AX ubiquitination, 53BP1 phosphorylation, and formation of DNA damage foci [7] (Figure 1). Recently, we showed that TRIM29 is a histone-binding protein responsible for DDR and that TRIM29 interacts with BRCA1-associated surveillance complex, cohesion, DNA-PKcs, and components of Tat-interactive protein 60 (TIP60) complex by cross talk between histone modifications [8] (Figure 1).…”
Section: Trim29 As An Oncogenic Regulatormentioning
confidence: 99%
“…However, a weak E3 ligase activity of TRIM29 mediated via B-box domain has recently been reported (15). In addition, following DNA damage, TRIM29 is phosphorylated and interacts with RNF8, an E3 ubiquitin ligase, which promotes DNA repair and cell survival (16). The TRIM family proteins are involved in a series of biological and physiological processes.…”
Section: Introductionmentioning
confidence: 99%